1977
DOI: 10.1007/bf00428597
|View full text |Cite
|
Sign up to set email alerts
|

Location of three key enzymes of gluconeogenesis in baker's yeast

Abstract: The subcellular location of hexose diphosphatase, phosphoenolpyruvate carboxykinase and pyruvate carboxylase in baker's yeast (Saccharomyces cerevisiae) was investigated by density gradient centrifugation of spheroplast lysates obtained by osmotic shock treatment of spheroplasts and centrifugation for 10000 g x min. On the evidence obtained from zonal separations these three enzymes of gluconeogenesis are most probably located in the soluble cytosol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Subcelhilar fractiona~ion of S. cerevisiae showed that pyruvate carboxylase is a cytosolic enzyme in this organism, in confirmation with earlier studies [6,8]. However, in contrast to the report by Evans et al [9], also in C. utilis the enzyme was exclusively recovered in the soluble fraction (Table I).…”
Section: Subcellular Localization and Activities Of Pyruvate-metaboiisupporting
confidence: 89%
See 2 more Smart Citations
“…Subcelhilar fractiona~ion of S. cerevisiae showed that pyruvate carboxylase is a cytosolic enzyme in this organism, in confirmation with earlier studies [6,8]. However, in contrast to the report by Evans et al [9], also in C. utilis the enzyme was exclusively recovered in the soluble fraction (Table I).…”
Section: Subcellular Localization and Activities Of Pyruvate-metaboiisupporting
confidence: 89%
“…However, the mitochondria were intact on the basis of various criteria and, furthermore, the enzyme was not detectable in the mitochondrial fraction. A cytosolic localization for pyruvate carboxylase in S. cerevisiae has also been reported by Haarasiha and Taskinen [6] and Lira et al [8]. Furthermore, no significant differences were found with respect to the kinetics of malate oxidation by isolated mitochondria.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For example, pyruvate carboxylase (enzyme 5 in scheme) might be in the cytoplasm as in baker's yeast (Haarasilta & Taskinen, 1977) though we have shown it in the mitochondrion which is its location in animal cells. There may be additional controls not examined in this work.…”
Section: Hypothesis For L I P I D a C C U M U L A T I O Nmentioning
confidence: 71%
“…Such a linkage would be advantageous if the oxaloacetate formed is predominantly utilised for biosynthetic purposes rather than for an enhancement of cycle flux, and could therefore provide a mechanism whereby a balance can be achieved in the use of glucose (or lactate) carbon in the synthesis of lipids and of amino acids and pyrimidines (tig.2). In accord with this postulate current evidence suggests that in S. cerevisiae pyruvate carboxylase is localised in the cytosol [36] , rather than in the mitochondrion as is the case invertebrates and invertebrates [6,33,34] . E. coli PEP carboxylase fails to show the characteristic transient activation on exposure to long chain acylCoAs which has been taken to indicate a membrane association in the case of pyruvate carboxylase from a thermophilic Bacillus [28] .…”
Section: Discussionmentioning
confidence: 90%